An Alternative to Incarceration: Co‐Occurring Disorders Treatment Intervention for Justice‐Involved Veterans. Issue 4 (December 2015) - Smelson, David A.; Pinals, Debra A.; Sawh, Leon; Fulwiler, Carl; Singer, Stephanie; Guevremont, Nathan; Fisher, William; Steadman, Henry J.; Hartwell, Stephanie
<x xml:space="preserve">Abstract</x> This article reports on the implementation, evaluation, and policy implications of MISSION‐Criminal Justice (CJ), an innovative intervention used to treat justice‐involved veterans with co‐occurring mental health and substance use disorders (CODs). In this pilot feasibility study, MISSION‐CJ was embedded into four Massachusetts courts and their probation services as an alternative to incarceration. Seventy‐six veterans were diverted from jail to MISSION‐CJ and completed intake and six‐month follow‐up assessments. The MISSION‐CJ participants were primarily white, had at least two prior arrests, served in a war combat zone, had a trauma before age 18, and had previously received mental health and substance use treatments. Preliminary six‐month follow‐up data suggested that the MISSION‐CJ participants showed improvements in COD problems, trauma symptoms, and a nonsignificant reduction in hospitalization/ER visits. MISSION‐CJ was feasible to implement and seemed to show some preliminary program success. A randomized controlled trial of MISSION‐CJ is a necessary next step in determining program efficacy. Policy implications for tailoring interventions for justice‐involved veterans such as MISSION‐CJ and their delivery alongside the court and probation are discussed.